2021
DOI: 10.4081/mm.2021.9684
|View full text |Cite
|
Sign up to set email alerts
|

First case of <em>Arthrographis kalrae</em> pulmonary infection in a patient with AIDS

Abstract: Arthrographis kalrae is a hyaline fungus. It is a saprophyte of the environment, mainly found in soil and compost. It is a rare isolate in clinical specimen. In recent years this pathogen has been attributed to various cases of opportunistic infections. Our patient was a 51-year-old Indian woman, farmer by occupation, who had HIV infection and was under HAART treatment. She presented with complaints of cough with scanty expectoration for 2 months. Her CD4 count was 75 cells/μl. Induced sputum was collected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…exhibited antibacterial activity against the four tested bacteria. Xi et al (2004) reported that Arthrographis kalrae cause panophthalmitis and invasive sinusitis infections in humans (Xi et al 2004) and lung infections in patients with AIDS (Samal et al 2021). However, other species of Arthrographis curvata produce lipases that has physicochemical properties that can be utilized for industrial or bioremediation purposes (Aamri et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…exhibited antibacterial activity against the four tested bacteria. Xi et al (2004) reported that Arthrographis kalrae cause panophthalmitis and invasive sinusitis infections in humans (Xi et al 2004) and lung infections in patients with AIDS (Samal et al 2021). However, other species of Arthrographis curvata produce lipases that has physicochemical properties that can be utilized for industrial or bioremediation purposes (Aamri et al 2020).…”
Section: Discussionmentioning
confidence: 99%